The needed competencies of secondary school principlas in Kedah - Mohamed Noor Rosli bin Baharom (Kulliyyah of Islamic Revealed Knowledge and Human Science, International Islamic University Malaysia, 1999)
This study investigates the needed competencies of secondary school principals in Kedah and the level of importance of each competency. The level of importance was determined using frequency distribution count. It also analyses the relationship between demographic background of the principals and the needed administrative competencies of secondary school principals in Kedah. A set of questionnaire consisting of 65 items was used in collecting data. The questionnaire was adapted from an instrument originally used for deputy principals in Australia. Adjustments were made using Harris's (1985) Competency Statements for Supervisory Performance and also to suit the administrative context of secondary schools in Malaysia. The respondents are secondary school principals of government schools in Kedah. The principals responded to the questionnaire, which were mailed to them adn returned using self-addressed envelopes. The questionnaires were administered by the principals. The data analysis involved simple statistics, frequency counts and percentages of responses to each item of the questionnaire. The study found that of the seven competencies, Staff Management was the most important category of which skills in listening to the concerns of staff, skills to lead and conduct meetings, and the knowledge in conducting staff performance appraisal ranked the higheest within the sub-groups also, some competencies are ranked much higher than others. The study also indicated that there are discernible patterns between experience as administrator and grade of school and the selected competencies.